Coercion and Cooperation in Cross-Strait Relations in Xi Jinping's Era (2012-2024) : The PRC, The ROC, The US - Serbin, Mikhail (My University, 2025)
This thesis explores the dynamics of coercion and cooperation in Cross-strait relations during Xi Jinping’s era (2012-2024), and focuses on relations between the People’s Republic of China (PRC), the Republic of China (ROC), and the United States (US). The paper employs historical institutionalist approach to examine how rotation within political institutions have influenced the balance of military, economic, and diplomatic strategies across the Taiwan Strait. The study identifies key institutions in charge of Cross-strait relations, and categorizes coercive tools (military intrusions, espionage, cyber operations) and coercive mechanisms (trade, educational exchanges, tourism). The results of the thesis indicate a great increase in applied coercive measures, coupled with continuous decline in cooperative patterns. These results are linked with political developments in the studied countries - centralization of power around Xi Jinping in China, and consolidation of power around the DPP in Taiwan. The findings of the thesis assign great importance to institutional changes and continuity, ideological alignment, and difference in regime types in shaping the relations between the PRC, the ROC, and the US.
Keywords: Cross-Strait Relations, People's Republic of China (PRC), Republic of China (ROC), United States (US), Xi Jinping